Cultural Heritage Preservation through Folktales as World Literature in Minahasa, Turkey, and Vietnam - Dewi Christa Kobis; Andriyani Marentek; Aditya Lapu Kalua; Yunaz Ali Akbar Karaman (OKARA: Jurnal Bahasa dan Sastra, 2025)
In the contemporary era of globalization and digital culture, local folktales continue to play a vital role in preserving cultural identity and moral values amid increasing cultural homogenization. This study explores how folktales from diverse cultures express universal human values and contribute to world literature. It analyzes six folktales from Minahasa (Indonesia), Turkey, and Vietnam—regions renowned for their rich oral storytelling traditions yet often underrepresented in comparative world literature research. The study addresses two central questions: Which universal themes are reflected in these folktales, and how do they exemplify David Damrosch’s three characteristics of world literature: circulation, transformation, and transcendence? Employing Damrosch’s theoretical framework, alongside the Aarne-Thompson-Uther (ATU) and Thompson’s Motif-Index classification systems, this qualitative comparative study identifies five recurring themes: transformation, love and sacrifice, rivalry, wisdom and betrayal, and moral justice. The findings reveal distinct levels of circulation, transformation, and transcendence among the folktales. While Minahasan folktales are more widely circulated within Indonesia, all six narratives exhibit adaptability and cross-cultural resonance, illustrating how local folktales safeguard cultural heritage while enriching global literary discourse. The study concludes that transcendence in world literature depends not only on circulation but also on a folktale’s capacity to convey universal human experiences through reinterpretation, translation, and cultural adaptation across societies.